Composite cryogels for dual drug delivery and enhanced mechanical properties. (13th June 2017) - de Lima, Gabriel G.; Traon, Fanny; Moal, Elouan; Canillas, Maria; Rodriguez, Miguel A.; McCarthy, Helen O.; Dunne, Nicholas; Devine, Declan M.; Nugent, Michael J.D.
Abstract : In this study, we present a simple and effective process that integrates hydrogels with drugs + ceramics via physical crosslinks resulting in improved mechanical properties. These cryogels have the potential for controlled drug release and stimulus responsive behavior. The hydrogels were produced from polyvinyl alcohol (PVA) and polyacrylic acid by varying the molecular weight of the polymers, via freeze‐thawing technique. The cryogels were combined with two ceramics: (1) a combination of beta‐tricalcium phosphate, wollastonite, magnesium silicate and (2) titanium dioxide nanopowder. Theophylline, a model drug, was incorporated into the structure to analyze the drug release behavior. A layered structure was produced by adding both hydrogels + ceramics into a mold where a PVA dried film acted as a barrier and reinforcing structure. The results showed that the barrier integrated between both hydrogels by a physically crosslinking mechanism. This adhesion was demonstrated using Fourier‐transform infrared spectroscopy and scanning electron microscopy. Swelling of this composite showed the profile of drug release from both hydrogels + ceramics while simultaneously releasing the drug independently without diffusing via the opposite layer. Finally, mechanical properties were improved with the addition of the ceramics, which demonstrates the potential approach in terms of modification of weak hydrogel systems. POLYM. COMPOS., 39:E210–E220, 2018. © 2017 Society of Plastics Engineers